Intracellular Ca2+ release and synaptic plasticity: A tale of many stores - Padamsey, Z; Foster, W; Emptage, NJ (SAGE Publications, 2018)
Ca2+ is an essential trigger for most forms of synaptic plasticity. Ca2+ signaling occurs not only by Ca2+ entry via plasma membrane channels but also via Ca2+ signals generated by intracellular organelles. These organelles, by dynamically regulating the spatial and temporal extent of Ca2+ elevations within neurons, play a pivotal role in determining the downstream consequences of neural signaling on synaptic function. Here, we review the role of three major intracellular stores: the endoplasmic reticulum, mitochondria, and acidic Ca2+ stores, such as lysosomes, in neuronal Ca2+ signaling and plasticity. We provide a comprehensive account of how Ca2+ release from these stores regulates short- and long-term plasticity at the pre- and postsynaptic terminals of central synapses.